Genetic variability of some agronomic traits in a collection of wheat (Triticum turgidum L. sp.pl.) genotypes under South Mediterranean growth conditions - Bendjama, Abdallah; Ramdani, Soumia (Italian Journal of Agronomy, 2022)
Some agronomic traits’ genetic variability was investigated in 60 tetraploid wheat accessions (Triticum turgidum L. sp.pl.) under rainfed conditions. The results indicated the presence of sufficient variability for all measured traits. The highest phenotypic and genotypic coefficient of variation was recorded for yield and awn length. High heritability coupled with high genetic advance and high expected response to selection recorded for thousand-grain weight, awn length, and the number of grains per spike. Cluster analysis grouped the 60 wheat genotypes into five clusters. Clusters are relatively formed according to the geographical origin of the genotypes. Cluster III carried entries having the best combinations for all the traits, in which genotypes PI 127106, PI 192658, PI 29051, and PI 67343 can represent an important reservoir of useful genes for the development of new wheat cultivars. Thousand-grain weight, biomass, awn length, and harvest index could be used as a selection criterion for hybridization programs in the future. Highlights - The genetic variability of 9 traits of 60 wheat varieties was investigated. - There was significant variability among wheat genotypes for all measured traits. - There were wheat varieties that showed the highest phenotypic and genotypic coefficient of variation. - Some wheat genotypes may be desired allele reservoirs. - Some traits can be an alternative in wheat selection.